2022
DOI: 10.1002/bkcs.12588
|View full text |Cite
|
Sign up to set email alerts
|

Excess dopant effect in platinum‐based alloys toward the oxygen electroreduction reaction

Abstract: Doping the PtNi octahedra with trace amount of transition metals has recently been shown to significantly improve the activity and durability of the oxygen reduction reaction (ORR). However, the role of excessive amounts of doped elements on ORR performance is unclear. In this work, PtNi octahedra were synthesized with and without excess Mo dopant. Also, spherical PtNi nanoparticles containing excess Co dopant were synthesized. The ORR performance revealed that PtNiMo octahedra and PtNiCo nanoparticles showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…PEMFCs are also currently considered as the preferred power source for mobile and stationary applications to replace the traditional combustion engine, and many countries have adopted PEMFC electric vehicles as the ultimate solution for green transportation. , Unfortunately, the electrode catalyst layer of PEMFCs requires platinum-group noble metal (PGM) catalysts for the target reactions of hydrogen oxidation (HOR) at the anode and oxygen reduction (ORR) at the cathode. The high cost and insufficient durability of PGM catalysts limit the large-scale application of PEMFCs . To achieve the widespread implementation of PEMFCs, it is critical to develop efficient electrocatalysts with high activity and durability. Recently, an important breakthrough with a ultra-low Pt alloy catalyst was achieved, showing a mass activity of 1.08 A mg Pt –1 and maintaining 64% of the initial value after 30,000 cycles in a PEMFC cathode application. However, the specific mass activity decreased by 1 order of magnitude in comparison with the value evaluated by using the rotating disk electrode (RDE) .…”
Section: Introductionmentioning
confidence: 99%
“…PEMFCs are also currently considered as the preferred power source for mobile and stationary applications to replace the traditional combustion engine, and many countries have adopted PEMFC electric vehicles as the ultimate solution for green transportation. , Unfortunately, the electrode catalyst layer of PEMFCs requires platinum-group noble metal (PGM) catalysts for the target reactions of hydrogen oxidation (HOR) at the anode and oxygen reduction (ORR) at the cathode. The high cost and insufficient durability of PGM catalysts limit the large-scale application of PEMFCs . To achieve the widespread implementation of PEMFCs, it is critical to develop efficient electrocatalysts with high activity and durability. Recently, an important breakthrough with a ultra-low Pt alloy catalyst was achieved, showing a mass activity of 1.08 A mg Pt –1 and maintaining 64% of the initial value after 30,000 cycles in a PEMFC cathode application. However, the specific mass activity decreased by 1 order of magnitude in comparison with the value evaluated by using the rotating disk electrode (RDE) .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, the high cost of PEMFC systems, the sluggish kinetics of the cathodic oxygen reduction reaction (ORR), and limited durability have hindered their widespread commercialization. [4][5][6] Previous studies have shown that sluggish ORR is associated with larger overpotentials and strong adsorption of reaction intermediates, which typically hinder proton and electron transfer during the reaction. [7][8][9][10] To overcome these hurdles and improve cell performances, platinum (Pt)-based nanocatalysts in various morphologies and shapes have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Low‐temperature fuel cells, such as proton‐exchange‐membrane fuel cells (PEMFCs), have great potential to facilitate a smooth energy transition away from fossil fuels and mitigate the current climate crisis [1–3] . However, the high cost of PEMFC systems, the sluggish kinetics of the cathodic oxygen reduction reaction (ORR), and limited durability have hindered their widespread commercialization [4–6] . Previous studies have shown that sluggish ORR is associated with larger overpotentials and strong adsorption of reaction intermediates, which typically hinder proton and electron transfer during the reaction [7–10] .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] However, traditional electroanalytical techniques used to investigate NPs have limitations when it comes to discerning the properties of individual NPs, as they rely on the ensemble behavior of NPs rather than examining single NPs individually. [22][23][24][25] Consequently, in recent years, single-entity electrochemistry (SEE) has gained popularity as a method for analyzing the electrocatalytic behavior of NPs at the single NP level. [26][27][28][29] The SEE signal is derived from the distinct electrocatalytic activities of active NPs when they interact with a less active supporting electrode, such as an ultramicroelectrode (UME).…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic performance of NPs is influenced by factors such as size, shape, capping agent, and surface lattice structure 19–21 . However, traditional electroanalytical techniques used to investigate NPs have limitations when it comes to discerning the properties of individual NPs, as they rely on the ensemble behavior of NPs rather than examining single NPs individually 22–25 . Consequently, in recent years, single‐entity electrochemistry (SEE) has gained popularity as a method for analyzing the electrocatalytic behavior of NPs at the single NP level 26–29 .…”
Section: Introductionmentioning
confidence: 99%